Cryoprotective Effect Oflow Sweetness Sugar On Physicochemical Properties Of Threadfin Bream (Nemipterus Spp.) Surimi During Frozen Storage - Nopianti, Rodiana (2011)
This study consists of two parts of experiment. The first experiment investigated the changes of physicochemical properties of threadfin bream surimi with different cryoprotectants (lactitol, maltodextrin, palatinit, polydextrose, sorbitol, sucrose, trehalose) at level 6% with 0.3% sodium tripolyphosphate (STPP) added in each surimi during six months of frozen storage. The analyses conducted included color, folding test, gel strength, expressible moisture, texture profile analyzer, scanning electron microscopy, Ca2+-ATPase activity, differential scanning calorimetry, moisture content, pH, protein solubility, sulfhydryl content, sodium dodecyl sulfate polyacrylamide gel electrophoresis, and water holding capacity.